Strategic Assumptions for The Success of Coal Mining Reclamation to be A Tourism Site; A Case Study in Rantau Pandan Village of Bungo Regency - asnelly ridha daulay (School of Postgraduate Studies, Diponegoro Univer, 2020)
Bad practice of open coal mining in Bungo Regency leaves many abandoned ponds. One pond in Rantau Pandan Village has been neglected for 5 years. Its environmental and social impacts pushed people to sue the government to revoke the permit of XXX Company that manages the mining. The low price of coal as well as the deep and large area to be piled make more difficult to do reclamation. This study aims at exploring the prospect of doing reclamation for tourism purposes with the concept of Community Based Tourism (CBT) and analyzing some strategic assumptions for the success that of reclamation. Primary data were collected through observation, interview and focus group discussion. Data were analyzed descriptively and qualitatively using Strategic Assumption Surfacing and Testing (SAST) method. Research finding shows that the people are eager to welcome the idea of CBT however the compensation from the mining company should be paid first. Of 22 assumptions for the development of tourism village, 18 assumptions can be grouped into quadrant II or Certain Planning Region, while 4 assumptions are in quadrant IV or Problematic Planning Region. To support this plan, it’s suggested five things i.e. resolving the social conflict among parties, strengthening the local institution, giving a mandate to villagers to manage the pond as a tourism site, then followed by supervising and enhance infrastructure to ease access.